Effect of calcium carbide residue and superplasticizer dosages on the mechanical and microstructural properties of fly ash based geopolymer composites - Gaddam Kalpana; Chappidi Hanumantha Rao; Musa Adamu; Ashwin Raut; Yasser E. Ibrahim (Open Ceramics)
The role of calcium-rich waste like Calcium carbide residue (CCR) in enhancing the performance of geopolymer remains inadequately explored. This study investigates the structural, mechanical, and microstructural behaviour of low-calcium fly ash (FA)-based geopolymer composites modified with varying CCR contents (0 %, 10 %, 20 %), sodium hydroxide molarities (8 M, 10 M, 12 M), and superplasticizer dosages (0 %, 1 %, 2 %). Results revealed that 10 % CCR combined with 2 % superplasticizer and 12 M NaOH offered optimal performance, achieving a 16.8 % increase in compressive strength, a 144.8 % rise in tensile strength (3.06 MPa), and a 145.5 % improvement in flexural strength (3.83 MPa). Flowability improved by 15 % with higher superplasticizer dosage, whereas excessive CCR (20 %) adversely affected strength and porosity. Microstructural observations confirmed the synergistic formation of N-A-S-H and C-S-H gels in optimized mixes. These findings highlight CCR’s viability as a sustainable calcium source in geopolymer technology, promoting enhanced mechanical performance and environmental sustainability through industrial waste valorisation.